MENINGKATKAN HASIL BELAJAR KETERAMPILAN MAKRAME MENGGUNAKAN METODE DEMONSTRASI PADA SISWA KELAS VIII 7 SMP NEGERI 3 SUNGAI LIMAU KABUPATEN PADANG PARIAMAN - NURISMAR HELMINARSIH Drs. Efrizal, M.Pd, Drs. Abd. Hafiz, M.Pd (Serupa The Journal of Art Education, 2014)
This study aims to determine the improvement of student learningoutcomes to subjects makrame skills in eighth grade 7 SMP Negeri 3 Lemons River District Pariaman totaling 23 people by using the method of demonstration. Data were collected using the research instruments and observation sheets. To see the change in students' learning activities in the two cycles are cycles I and II. The data were obtained and analyzed using percentages. The study findings suggest that increased learning outcomes significantly makrame skills, it can be seen from the average pre-cycle 66 to 73 in cycle I. In the second cycle was also shown to increase with an average of 79.57. It can be concluded that the method can improve learning outcomes Demonstration makrame skills Eighth Grade 7 students at SMP Negeri 3 Lemons River Padang Pariaman.Key words: Metode Demonstrasi, Peningkatan Hasil Belajar. Pelajaran Keterampilan Makrame kelas VIII 7 SMP Negeri 3 Sungai Limau Kabupaten Padang Pariaman.